Comparison of thermal and electrical performance in a HCPV system based on spray cooling. (1st May 2023) - Chen, Haifei; Wang, Yunjie; Yang, Huihan; Cai, Jingyong; Zhang, Tao; Yang, Jie
Highlights: A SC-HCPV system is proposed to improve temperature uniformity of solar cells. The temperature uniformity, thermal and electrical performance are extensively analyzed. Compared with partial jet, SC-HCPV has better thermal and electrical properties. Abstract: As a renewable energy, solar energy can effectively solve the energy crisis. Improving the efficiency of thermal and electrical conversion is of significance to high concentration photovoltaic/thermal (HCPV/T) systems. For further reducing the contact thermal resistance in the HCPV/T systems, this paper presents an integrated system of HCPV system and spray cooling (SC-HCPV). A comprehensive heat transfer model was established to study the influence of heat on solar cells by combining solar cells with spray cooling (SC). The temperature uniformity, thermal and electrical performance at high concentrations is studied through experiments and simulations. The influences of nozzle settings, concentration ratio (CR) and inlet temperature are evaluated to get suitable system operating parameters. Compared with the partial jet, the EEF under SC is 2.1% higher than that under the partial jet, and the solar cell power generation per unit area can gain 7.5%. For another aspect, the EEF of the system can still maintain above 30% under the high CR of 1000, and high-temperature hot water above 60 °C can be obtained, which has superior potential applications in printing and dyeing, domestic water with high temperature, seawater desalination, disinfection water and so on.